Особливості «великого терору» 1937–1938 рр. на Дніпропетровщині - Ченцов, В.; Архірейський, Д. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
The article is dedicated to the regional peculiarities of «the great terror» of 1937–1938 in Dnipropetrovs’k region.